2016
DOI: 10.3390/met6050096
|View full text |Cite
|
Sign up to set email alerts
|

Joining of TiAl to Steel by Diffusion Bonding with Ni/Ti Reactive Multilayers

Abstract: Dissimilar diffusion bonds of TiAl alloy to AISI 310 stainless steel using Ni/Ti reactive multilayers were studied in this investigation. The Ni and Ti alternating layers were deposited by d.c. magnetron sputtering onto the base materials, with a bilayer thickness of 30 and 60 nm. Joining experiments were performed at 700 and 800˝C for 60 min under pressures of 50 and 10 MPa. The effectiveness of using Ni/Ti multilayers to improve the bonding process was assessed by microstructural characterization of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Reactive multilayer thin films are an alternative interlayer for reducing the temperature and/or the pressure needed for diffusion bonding. These multilayers can improve the diffusivity, due to their nanocrystalline nature and high density of defects, and simultaneously act as a local heat source, as the result of the heat released by the exothermic reaction of the multilayers to form intermetallic compounds [15][16][17][18][19][20]. Previous studies [15][16][17] have shown that Ni/Al multilayers are effective in the diffusion bonding of TiAl to themselves [15], to steel [16] and to Ni-based superalloys [17].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive multilayer thin films are an alternative interlayer for reducing the temperature and/or the pressure needed for diffusion bonding. These multilayers can improve the diffusivity, due to their nanocrystalline nature and high density of defects, and simultaneously act as a local heat source, as the result of the heat released by the exothermic reaction of the multilayers to form intermetallic compounds [15][16][17][18][19][20]. Previous studies [15][16][17] have shown that Ni/Al multilayers are effective in the diffusion bonding of TiAl to themselves [15], to steel [16] and to Ni-based superalloys [17].…”
Section: Introductionmentioning
confidence: 99%
“…For cleaning, sonicating in surfactant solutions and rinsing with acetone or isopropanol are employed [6].…”
Section: Contamination and Formation Of Burrsmentioning
confidence: 99%
“…Promising studies have revealed that reactive multilayers are an auspicious interlayer for bonding similar and dissimilar titanium alloys. Particularly, Ni/Al and Ni/Ti multilayers provide a unique opportunity to drastically improve conventional bonding technologies by acting as local heat sources and enhancing the diffusivity across the interface [15][16][17][18]. This may be a good approach to apply to diffusion bonding between metals and ceramics in order to produce joints with desirable mechanical properties.…”
Section: Diffusion Bondingmentioning
confidence: 99%
“…Conventional titanium alloys are continuously challenged by the operation at temperatures higher than 550 • C due to poor high temperature oxidation resistance and creep properties [2]. Whence, the investigations on the production, characterization, and joining of titanium alloys as titanium aluminides (TiAl), TiNi and Ti6Al4V, have increased during the last decades [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%